Two new species of Sochinsogonia (Hemiptera: Cicadellidae: Cicadellinae) from Philippines - Feng, Ling; Dietrich, Christopher H.; Zhang, Yalin (Zootaxa, 2018)
Two new species, Sochinsogonia multimacula and S. radicalia spp. nov., of the genus Sochinsogonia Young from Philippines are described and illustrated. A key to distinguish this genus from closely related Oriental genera is provided. A species checklist of the genus is also provided.